Reacciones adversas a la transfusión de componentes sanguíneos (2017)
Introduction: The use of blood as a therapeutic option to improve the quality of life of many patients generates a high impact on the provision of health services, however, it is important to establish a risk-benefit comparison and thus ensure a reliable therapy and safe. Numerous strategies have been implemented by blood banks and transfusion medicine services to reduce ITTX (transfusion-transmitted infections), but there are still situations of adverse reactions to transfusion that compromise the quality of life of recipients. Objective. Describe the distribution of transfusion reactions most frequently developed by blood recipients, depending on the type of component they receive. Materials and methods A review of different bibliographies databases was made based on a search in different bibliographic sources and in databases such as Scopus, ScienceDirect, EBSCO, EMBASE, including articles in Spanish and English, those that were since 2012 were selected Until 2017. Results. Acco According to the literature reviewed it is estimated that adverse reactions to GRE transfusion are 40%, followed by platelets in 32% plasma 27%, and total blood in 1%. The most frequent adverse reactions to blood transfusion are the immediate ones, where allergic reactions prevail when transfused packed red blood cells, platelets, plasma and cryoprecipitate, the non-hemolytic febrile reaction is another of the most frequent reactions, where the component mainly Associated are GRE, and to a lesser extent TRALI and hypotension. Delayed adverse reactions are infrequent, however, the most common within this group is late haemolytic reaction. riding to the literature reviewed it is estimated that adverse reactions to GRE transfusion are 40%, followed by platelets in 32% plasma 27%, and total blood in 1%. The most frequent adverse reactions to blood transfusion are the immediate ones, where allergic reactions prevail when transfused packed red blood cells, platelets, plasma and cryoprecipitate, the non-hemolytic febrile reaction is another of the most frequent reactions, where the component mainly Associated are GRE, and to a lesser extent TRALI and hypotension. Delayed adverse reactions are infrequent, however, the most common within this group is late haemolytic reaction.